A macro–microscopic coupled consolidation model for saturated porous media with compressible constituents. (December 2021) - Liang, Jia-Yu; Li, Yue-Ming
Abstract: Porosity is an important variable in consolidation theory. However, porosity information is missing in Biot's model when the solid constituent of the porous media is assumed to be compressible. This paper develops a macro–microscopic coupled consolidation model in order to track the evolution of the porosity for saturated porous media with compressible constituents. The proposed model exploits a u − ε v sr − p form with the aim to incorporate the coupled behavior between the macroscopic and microscopic volumetric compressibility. Subsequently, a specific study on the analytical solutions for the case of a linear-loaded one-dimensional consolidation problem based on the proposed model is presented. Two examples are shown in order to demonstrate how to apply the proposed model. The proposed model paves the way to study the consolidation problem with porosity-dependent coefficients for saturated porous media with compressible constituents.